Unsur Pelayanan Sesuai Survei Kepuasan Masyarakat (SKM) Dengan Kepuasan Peserta Jaminan Kesehatan Nasional Di Puskesmas Liya,Wangi-Wangi Selatan Kabupaten Wakatobi - Dyah Fauziah Ilyas; Asriati Asriati; La Ode Alifariki (Gaster, 2020)
Background: The Community Satisfaction Survey is a comprehensive measurement activity on the level of community satisfaction with the quality of services provided by public service providers. Community Satisfaction Survey Elements are requirements, mechanism and procedure systems, Settlement Time, Cost / Tariff, Product Specifications Type of Service, Competence Executor, Implementing Behavior, facilities and infrastructure, Handling Complaints, Suggestions and Feedback. Research Purpose: to determine the relationship of service elements in accordance with the Community Satisfaction Survey with the satisfaction of national health insurance participants at the Liya Wangi-Wangi Health Center south of Wakatobi Regency. Research Methods: This study used an analytical-observational method with a cross sectional approach. The population of this study were patients who participated in National Health Insurance at the South Liya Wangi-Wangi Health Center in Wakatobi Regency with a population of 600. With a sample of 120 samples taken using accidental sampling method . Data on service elements and patient satisfaction were obtained through questionnaires. Data analysis used the Spearman rank correlation test method and was considered significant if p <0.05. Research Results: The results of this study indicate the level of satisfaction of each element of service, namely service requirements 12.5% very good, 87.5% good, 0.0% less good, system services, mechanisms and procedures 52.5% very good, 47.5% good, 0.0% less good , service completion time 47.5% is very good, 52.5% is good, 0.0% is not good, service costs / rates are 100% very good, 0.0% is good and 0.0% is not good, product service specifications type service 61.7% are very good, 38.3% good, 0.0% is not good, service executive competence 42.5% is very good, 57.5% is good, 0.0% is not good, service behavior of executors 68.3% is very good, 31.7% is good, 0.0% is not good, service for handling complaints and input 35.5% is very good, 64.2% good, 0.0% not good, elements of facilities and infrastructure 53.3% very good, 30.0% good, 16.7% not good. The results of the analysis show that the significant level (sig) is 0,000 (<0.05) which means that there is a significant relationship between the elements of service to patient satisfaction the amount of the Spearman Rank correlation coefficient is 0.681. Conclusion: The conclusion of this study, there is a relationship between the elements of service and satisfaction of participants of the National Health Insurance at the Liya Wangi-Wangi Selatan Health Center in Wakatobi Regency